Monetary policy and wage bargaining in the EMU: Restrictive ECB policies, high unemployment, nominal wage restraint and rising inflation - Eckhard Hein (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2002)
Assessing the effects of monetary policy and wage bargaining on employment and inflation in the European Monetary Union (EMU), in the first step a Post-Keynesian competitive claims model of inflation with endogenous money is developed. In this model the NAIRU is considered to be a short-run limit to employment enforced by independent and conservative central banks. In the long run, however, the NAIRU will follow actual unemployment and is therefore also dependent on the forces determining aggregate demand, including monetary policies. But the NAIRU may also be reduced by effectively co-ordinated wage bargaining as has been shown by institutional political economists. Applying these considerations to the economic performance of the EMU, different scenarios determined by wage bargaining coordination and the European Central Bank.s (ECB) monetary policies are developed. It is shown that the first phase of EMU was dominated by uncoordinated wage bargaining across EMU and an .anti-growth-bias. of the ECB. Therefore, the Euro area was plagued with nominal wage restraint, high unemployment and rising inflation. Economic performance will improve if the ECB abandons its asymmetric monetary strategy. This may be facilitated by a higher degree of effective wage bargaining co-ordination across EMU.
Keywords: E12; E24; E31; E58; 330; European Monetary Union; monetary policy; wage bargaining; inflation and employment; Geldpolitik; Lohnverhandlungen; Tarifpolitik; Europäische Wirtschafts- und Währungsunion; Inflationstheorie; Postkeynesianismus; Beschäftigungseffekt; Theorie